Indirect discrimination is not necessarily unjust - Lippert-Rasmussen, K (Oxford Uehiro Centre for Practical Ethics, 2014)
This article argues that, as commonly understood, indirect discrimination is not necessarily unjust: 1) indirect discrimination involves the disadvantaging in relation to a particular benefit and such disadvantages are not unjust if the overall distribution of benefits and burdens is just; 2) indirect discrimination focuses on groups and group averages and ignores the distribution of harms and benefits within groups subjected to discrimination, but distributive justice is concerned with individuals; and 3) if indirect discrimination as such is unjust, strict egalitarianism has to be the correct account of distributive justice, but such egalitarianism appears vulnerable to the leveling down objection (whether decisively or not), and many theorists explicitly reject strict egalitarianism anyway. The last point threatens the position of liberals who oppose indirect discrimination but think significant inequalities can be just.